Measuring Teacher Productivity At SMPIT Ma'arif Padang Panjang: An Empirical Analysis - Anas, Iqbal; Sesmiarni, Zulfani (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
This study aims to measure and analyze teacher productivity at SMPIT Ma'arif Padang Panjang through an empirical approach. Teacher productivity is a key factor in improving the quality of education and learning in schools. The research method used is a quantitative method with a survey approach, where data is collected through questionnaires distributed to teachers at SMPIT Ma'arif Padang Panjang. Data analysis was conducted using descriptive and inferential statistics to identify the level of productivity and the factors that influence it. The results show that teacher productivity at SMPIT Ma'arif Padang Panjang is at a fairly good level, but some areas require improvement. Factors that contribute positively to productivity include the availability of educational resources, administrative support, and training and professional development. Conversely, factors such as excessive workload and lack of incentives are considered to hinder productivity. This study provides practical recommendations for school management to improve teacher productivity, including through improving supporting facilities, providing ongoing training programs, and implementing a fair incentive system. The implications of this study are expected to help in formulating more effective and efficient education policies, to improve the quality of education at SMPIT Ma'arif Padang Panjang.   Keywords: Teacher Productivity, SMPIT Ma'arif Padang Panjang, Empirical Analysis, Education Quality, Productivity Factors